Multi-proxy analysis of relative sea-level and paleoshoreline changes during the last 2300 years in the Campi Flegrei caldera, Southern Italy. (20th November 2021) - Aucelli, Pietro P.C.; Mattei, Gaia; Caporizzo, Claudia; Cinque, Aldo; Amato, Lucio; Stefanile, Michele; Pappone, Gerardo
Abstract: This study aims to present new additional data regarding the relative sea-level (RSL) changes and the vertical ground movements (VGM) occurred in Campi Flegrei caldera since the Early Roman period (3rd century BC), commenting also on the accompanying changes of the coastal landscape and its implications in terms of human adaptation. The study area is located along the western sector of the Campi Flegrei caldera, one of the active volcanic systems of the Mediterranean region that started its activity more than 60 ka BP. Despite the human occupation of Campi Flegrei started not later than the Early Bronze Age (about 3.5 ka BP) and the earliest coastal settlements date back to the first Greek colonization of Southern Italy (ca. 800 BC), nowadays, the numerous coastal archaeological sites that are scattered in the studied area belong to the Roman period. The geoarchaeological interpretation of these remains allows detecting and dating of ancient positions of relative sea levels (RSLs), reconstructing of past coastal conformations, and measuring ancient VGM. The coastal sector between the modern Baia and Miseno was surveyed with a transdisciplinary and multi-proxy approach by means of direct and indirect methods, including, among others, paleo-environmental and archaeo-stratigraphic well logs analysis, geo-acoustic maps interpretation, and measurements of archaeological indicators of ancient sea levels. By comparing our measurement of RSL with the eustatic models of Peltier (2004) and Lambeck et al. (2011), the VGMs history of the coastal sector in the last 2300 years was reconstructed. Even if several volcano-tectonic oscillations were recorded, the obtained multi-proxy indications allow reconstructing two different behaviours in terms of vertical displacements: an overall subsiding trend affecting the area between the Early Roman period and the Middle Age, and a prevailing uplift after that period. The main coastal changes that occurred in the same period can be summarized in a coastal retreat ranging between 40 and 300 m, mainly due to the submersion of the pre-existing coastal area and leading to the submersion of villas, thermae, and other structures built on it. However, based on our measurements, the time span covered by the high-resolution data obtained from the three fish tanks here studied (60 BC – 12 AD) appears to be a period of volcano-tectonic stability, without significant VGMs.